Into the Blue. The Visualization of Building Walls and Transgressing Borders in Scandorama by Hannele MikaelaTaivassalo and Catherine Anyango Grünewald (Altre Modernità, 2021)
This essay examines Scandorama, a graphic novel from 2018 scripted bythe Finland-Swedish writer Hannele Mikaela Taivassalo and drawn by the Kenyan-Swedish artist Catherine Anyango Grünewald. The work is read as a comment tounsettling trends in contemporary Scandinavia such as rising nationalisms, antiimmigrantsentiments, and the destruction of nature. Special attention is given to howthe issues of building walls and transgressing borders are recorded not only on averbal level but, first and foremost, to the ways in which these concerns are entrustedto the visual code of comics. It is argued that the chromatic structure employed in thebook creates a visual subtext expressing the dystopian theme embedded inScandorama. Through the use of a single colour, blue, in a monochrome storyworld,the idea of erecting walls and transgressing borders is backed up and expressed in atleast three contexts investigated in the article: (1) ‘othering’; (2) architecture; (3) bodyand mind. Here, the dramaturgical potential of colour combines with motives such asgovernment surveillance, loss of individualism, genetic engineering, futuristictechnology, environmental destruction, and urban settings to produce a dystopian‘blueprint’.